1996
DOI: 10.1042/bj3170503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multiple cytokines plus bacterial endotoxin on glucose and nitric oxide production by cultured hepatocytes

Abstract: Treatment of cultured hepatocytes with a combination of cytokines, including tumour necrosis factor-alpha, interferon-gamma and interleukin-1 beta, plus lipopolysaccharide resulted in a time-dependent induction of nitric oxide (NO) synthase (as measured by NO2- (+) NO3- production) and inhibition of hepatic gluconeogenesis and glycogen breakdown. The inhibition of glucose release was comparable with the observed following treatment of rats with lipopolysaccharide or treatment of isolated hepatocytes with artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…We have previously found that AM3 inhibits LPS-induced TNF-a expression in peritoneal macrophages [14], which are a rich source of iNOS and contributes to NO accumulation during endotoxemia [17]. On the other hand, TNF-a up-regulation has been shown to induce iNOS expression [18], therefore the effect of AM3 on iNOS expression could be explained by its inhibitory effect on pro-inflammatory cytokines. Conversely, iNOS inhibitors down-regulate TNF-a synthesis [19].…”
Section: Resultsmentioning
confidence: 97%
“…We have previously found that AM3 inhibits LPS-induced TNF-a expression in peritoneal macrophages [14], which are a rich source of iNOS and contributes to NO accumulation during endotoxemia [17]. On the other hand, TNF-a up-regulation has been shown to induce iNOS expression [18], therefore the effect of AM3 on iNOS expression could be explained by its inhibitory effect on pro-inflammatory cytokines. Conversely, iNOS inhibitors down-regulate TNF-a synthesis [19].…”
Section: Resultsmentioning
confidence: 97%
“…There were many reports to examine the effects of cytokines and NO after endotoxemia (Lee et al, 2002a;Moncada et al, 1991;ter Steege et al, 2000). The experiments were performed in anesthetized animals or various cell lines culture with only 4 -6 h of monitoring (Buttery et al, 1994;Ceppi et al, 1996;Liu et al, 1996;Mailman et al, 2001;Pedoto et al, 2002;Preiser et al, 2001;ter Steege et al, 2000). These situations were different from the clinical patients with endotoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, the possibility remains that LPS sensitizes the immature brain by lowering blood glucose, as LPS has previously been shown to reduce blood glucose levels through a decrease in gluconeogenesis and glycogenolysis [Goto et al, 1994;Ceppi et al, 1996]. In addition, acute lowering of blood glucose with insulin prior to HI increased brain injury, while a gradual lowering of glucose induced by fasting did not affect brain damage [Yager et al, 1992].…”
mentioning
confidence: 99%